Pemodelan Causal Loop Diagram Percepatan Proyek terhadap Biaya dan Kualitas Konstruksi: Pemodelan Causal Loop Percepatan Proyek terhadap Biaya dan Kualitas Konstruksi - D. Maharani, Avrilia; R. Winanda, Lila Ayu; Wijayaningtyas, M.; Kartika, Deviany (Tadulako University, 2026)
Construction project acceleration is a strategy commonly implemented to overcome schedule delays; however, its application often results in increased costs and reduced work quality when not managed in a systematic and integrated manner. This condition reflects the presence of complex and dynamic interrelationships among time, cost, and quality as the three main elements within the triple constraint framework, which cannot be adequately analyzed using linear approaches. Failure to understand the interactions among these three aspects may lead to project inefficiencies and decreased overall performance. Therefore, an approach capable of explaining cause–effect relationships and feedback mechanisms within construction project systems is required. This study aims to model the causal relationships between project acceleration, cost, and quality in order to obtain a structural understanding of their dynamic interactions. The research method employs a system dynamics approach using causal loop diagram modeling supported by Vensim PLE 10.4.0 software. The research stages include system definition to determine boundaries and identify key variables, model formulation based on a literature review to establish intervariable relationships, and the development of causal loop diagrams to illustrate interactions and feedback structures within the system. The modeling results indicate that the developed system consists of twenty feedback loops and forty-six one-way relationships representing interactions among acceleration, cost, and quality factors within the context of project acceleration. These findings confirm that project acceleration, cost, and quality are not independent variables but are dynamically interconnected. The proposed model provides a conceptual contribution to strengthening systemic understanding in construction project management and can serve as a foundation for strategic decision-making related to more effective and sustainable project acceleration